2023
DOI: 10.1038/s41467-022-35720-5
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial Hsp70 controls the assembly of the F1FO-ATP synthase

Abstract: The mitochondrial F1FO-ATP synthase produces the bulk of cellular ATP. The soluble F1 domain contains the catalytic head that is linked via the central stalk and the peripheral stalk to the membrane embedded rotor of the FO domain. The assembly of the F1 domain and its linkage to the peripheral stalk is poorly understood. Here we show a dual function of the mitochondrial Hsp70 (mtHsp70) in the formation of the ATP synthase. First, it cooperates with the assembly factors Atp11 and Atp12 to form the F1 domain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Several studies have shown that the loss of F1 domain assembly factors results in the decreased abundance of F1 domain in yeast, such as FMC1 [68,69]. On the contrary, we found that the loss of PHB3 results in the accumulation of the F1 domain and does not affect the assembly of the F1 domain into ATP synthase in Arabidopsis (Figure 3C,D).…”
Section: The Loss Of Phb3 Decreases the Activity Of Atp Synthase And ...contrasting
confidence: 50%
“…Several studies have shown that the loss of F1 domain assembly factors results in the decreased abundance of F1 domain in yeast, such as FMC1 [68,69]. On the contrary, we found that the loss of PHB3 results in the accumulation of the F1 domain and does not affect the assembly of the F1 domain into ATP synthase in Arabidopsis (Figure 3C,D).…”
Section: The Loss Of Phb3 Decreases the Activity Of Atp Synthase And ...contrasting
confidence: 50%
“…The 'black box' nature of these AI systems makes it difficult to investigate why a model generates a specific response, which poses challenges in ensuring accountability and trustworthiness, especially in critical applications. 64 Reliance on external validation: Due to these limitations, outputs from GPT-4 often require external validation. Users must cross-check information with reliable sources, especially for critical applications.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…Together with DNAJA3 (mtHsp40/TID-1) and Grpe1/Grpe2 (Pam16/18), Mortalin aids in mitochondrial DNA replication, regulation, and maintenance 38 , 44 as well as the import and assembly of mitochondrial respiratory complexes. 45 J proteins such as DNAJA3 play a crucial role in delivering client proteins to the Hsp70, preventing client protein aggregation, and stimulating the ATPase activity of Hsp70, aiding in client binding and release. 46 Grpe1 recruits the J-protein Grpe2 to regulate the ATPase activity of Mortalin.…”
Section: Mitochondrial Chaperone Codementioning
confidence: 99%